I believe it’s B sorry if I’m wrong
(f.g)(x) = f (g(x))= f ( x^4+3)
= (x^4+3)^2 + 2 ( x^4+3) - 6
= x^8 + 9 + 6x^4 + 2x^4 + 6-6
= x^8 + 8x^4+9
Answer:
This series is divergent
F
Step-by-step explanation:
we are given a series
Firstly, we will find nth term
Numerator:
3, 4, 5,...
so, nth term will be
![a_n=n+3](https://tex.z-dn.net/?f=a_n%3Dn%2B3)
Denominator:
4,5,6,....
so, nth term will be
![b_n=n+4](https://tex.z-dn.net/?f=b_n%3Dn%2B4)
so, we can find it's nth term as
![c_n=\frac{n+3}{n+4}](https://tex.z-dn.net/?f=c_n%3D%5Cfrac%7Bn%2B3%7D%7Bn%2B4%7D)
we can use divergent test
![\lim_{n \to \infty} c_n=\lim_{n \to \infty} \frac{n+3}{n+4}](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%20c_n%3D%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Cfrac%7Bn%2B3%7D%7Bn%2B4%7D)
we can divide top and bottom by n
![\lim_{n \to \infty} c_n= \lim_{n \to \infty} \frac{n/n+3/n}{n/n+4/n}](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%20c_n%3D%20%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Cfrac%7Bn%2Fn%2B3%2Fn%7D%7Bn%2Fn%2B4%2Fn%7D)
![\lim_{n \to \infty} c_n= \lim_{n \to \infty} \frac{1+3/n}{1+4/n}](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%20c_n%3D%20%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Cfrac%7B1%2B3%2Fn%7D%7B1%2B4%2Fn%7D)
now, we can plug n=inf
![\lim_{n \to \infty} c_n= \frac{1+0}{1+0}](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%20c_n%3D%20%5Cfrac%7B1%2B0%7D%7B1%2B0%7D)
![\lim_{n \to \infty} c_n=1](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%20c_n%3D1)
Since, it is non-zero value
so, this series is divergent
Answer:
A. -4-3x>7
Step-by-step explanation:
-4-3(-5)>7
-4-(-15)>7
11>7
Answer:
The slope is 2
Step-by-step explanation:
Y = mx+b y = mx+b is the shape of the slope-intercept where m is the slope.